Sosialisasi tentang Covid-19 dan Vaksinasi Covid-19 sebagai Upaya Mengurangi Kecemasan di Nufuak, Belu-NTT - Sefrina Maria Seuk Asa; Maria Julieta Esperanca Naibili; Rufina Nenitriana S. Bete (Humanism: Journal of Community Empowerment (HJCE), 2022)
The impact of the Covid-19 pandemic is not only in the health aspect but also has major implications for the political, economic, socio-cultural, educational, religious, and community welfare aspects. The time for the end of the Covid-19 pandemic is still unknown. Although there is already a vaccine, there is no specific therapy or drug for Covid-19. Not to mention the problems faced such as the threat of SARS-COV-2 mutation with new variants, as well as public attitudes to health protocol discipline are still the main challenges, which at times can cause a new wave of national or global Covid-19 pandemics. This activity aims to reduce public anxiety through counseling to increase knowledge, motivation and change people's behavior in implementing health protocols related to Covid-19. Community service activities related to Covid-19 education and Covid-19 vaccination. The method used in the implementation of science and technology activities to the community is disseminated in the form of two-way lectures and discussions, as well as the distribution of leaflets. In the final interview and observation, it showed changes and improvements, namely 85% of participants knew and understood that Covid-19 could be prevented by complying with and implementing the 5M health protocol; 50% of participants took the initiative to register at the Puskesmas/Clinic which facilitates vaccination services to the wider community in order to obtain the first dose of vaccination; and 10% of participants have started to register at the Fatukbot Headman office and the South Atambua Health Center for Covid-19 vaccination